Analisis Sistem Saluran Drainase dalam Upaya Penanggulangan Banjir di Jalan Ciledug Raya, Kelurahan Cipulir, Kecamatan Kebayoran Lama, Jakarta Selatan - Dwi Rizki Rahmawati; Arris Maulana; Henita Rahmayanti (INDO PUBLISHING, 2025)
This study aims to analyze the condition of the drainage system along Jalan Ciledug Raya, located in Kelurahan Cipulir, Kecamatan Kebayoran Lama, South Jakarta, as part of efforts to mitigate flooding. Flooding in this area frequently occurs, particularly during the rainy season with high rainfall intensity. The research employed a quantitative descriptive approach using both primary and secondary data analysis techniques. Rainfall data were obtained from the Kemayoran Station and South Tangerang Climatology Station over a 10-year period (2015–2024). Rainfall analysis utilized the Log Pearson Type III distribution method, while the planned flood discharge (Qr) was calculated using the Rational Method. The results showed that the capacity of the existing drainage channel (Qs), at 5.379 m³/s, is lower than the planned flood discharge, which is 8.215 m³/s for a 2-year return period and 9.395 m³/s for a 5-year return period. These findings indicate that the current drainage infrastructure is insufficient to accommodate the planned flood discharge, resulting in surface water accumulation. Additional contributing factors include sedimentation and low public awareness regarding environmental cleanliness.